Monetary policy transmission to mortgages in a negative interest rate environment - Adrien Amzallag; Alessandro Calza; Dimitris Georgarakos; Jo\~ao Sousa (European Central Bank (ECB), 2019)
Do negative policy rates hinder banks' transmission of monetary policy? To answer this question, we examine the behaviour of Italian mortgage lenders using a novel loan-level dataset. When policy rates turn negative, banks with higher ratios of retail overnight deposits to total assets charge more on new fixed rate mortgages. This suggests that the funding structure of banks may matter for the transmission of negative policy rates, especially for long-maturity illiquid assets. Nevertheless, the aggregate economic implications for households are small, suggesting that concerns about inefficient monetary policy transmission to households under modestly negative rates are likely overstated.
Keywords: E40; E52; E58; G21; 330; monetary policy; negative interest rates; bank lending; mortgages ECB